Evolusi Konsep Pembelajaran Bahasa Arab: Tinjauan Sistematis terhadap Orientasi Pembelajaran Klasik dan Kontemporer - Gufron Zainal Abidin Sdawi Manasiq (Universitas Al-Amien Prenduan, 2022)
This research aims to explore the changes in concepts and orientations in the teaching of the Arabic language from classical to contemporary times. The study adopts a qualitative approach with a literature review type of research focusing on scholarly works discussing the topic. The data sources include academic literature such as reference books and published journal articles. Content analysis is employed as the data analysis method. The research findings indicate that the evolution of concepts and orientations in teaching the Arabic language from classical to contemporary represents a journey focused on adapting to changing times. From a strong traditional foundation, through the influence of technology and an emphasis on communicative skills, to the integration of rich traditional values, these changes depict an evolution that allows Arabic language learning to be more relevant and effective in addressing the challenges of the present era.Â Â